2017
DOI: 10.18632/oncotarget.19600
|View full text |Cite
|
Sign up to set email alerts
|

Impact of marital status on renal cancer patient survival

Abstract: Marital status is an independent prognostic factor for various cancer types. The present study used the Surveillance, Epidemiology, and End Results (SEER) database of the National Cancer Institute (NCI) to analyze the impact of marital status on renal cancer patient survival outcomes. We identified a total of 62,405 eligible patients (23,800 women and 38,605 men). Overall 5-year renal cancer cause-specific survival (CSS) was 80.3% in the married group, 69.2% in the widowed group, 78.9% in the single group, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
12
2
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 34 publications
(37 reference statements)
3
12
2
2
Order By: Relevance
“…Similar results were observed in patients with renal cancer 34. Prior studies have indicated that the social and mental support provided by marriage is different across different races.…”
Section: Discussionsupporting
confidence: 83%
“…Similar results were observed in patients with renal cancer 34. Prior studies have indicated that the social and mental support provided by marriage is different across different races.…”
Section: Discussionsupporting
confidence: 83%
“…Herein, we used SEER data to elucidate whether insurance status, in addition to ethnicity, age, and SEER stage, among other factors, may play an important role in the survival disparity. Besides, in Wang et al's report, [ 14 ] a total of 62,405 eligible patients diagnosed between 2004 and 2013 were enrolled; however, in our study, an even bigger sample of 97,662 eligible patients diagnosed between 1973 and 2013 were included. Additionally, in Miao et al's report, [ 15 ] the kidney cancer patients included both renal cancer and renal pelvis cancer patients; the pathology of these 2 types of cancer is completely different.…”
Section: Discussionmentioning
confidence: 77%
“…Actually, we made a further analysis to seek out possible explanations for the survival difference. In both previous studies, [ 14 , 15 ] insurance status was not included as a covariate, and the effect of insurance on the survival outcome of patients with renal cancer was not considered. Herein, we used SEER data to elucidate whether insurance status, in addition to ethnicity, age, and SEER stage, among other factors, may play an important role in the survival disparity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is postulated that married status could contribute to optimistic psychological, enough social support, decent incomes, healthy lifestyle and comfortable living conditions. Similarly, previous studies reported that that marital status was a prognostic factor of survival in kidney cancer patients9-11. However, all of them merely focus on all kinds of kidney cancer without differentiating pathological subtypes.…”
Section: Introductionmentioning
confidence: 88%